The UN Security Council’s Strategy for Multilateralism in the Context of Great Power Competition - Lulu Yang (Studies in Social Science & Humanities, 2025)
This paper explores in depth how the UN Security Council responds to the challenges in global governance through the strategy of multilateralism in the context of the current great power competition. In the specific study, the main focus is to analyze in detail how the Security Council adapts to the new dynamics brought about by great power competition, so as to conclude that in the context of great power competition, the UN Security Council’s strategy of multilateralism is crucial to the effectiveness of the global governance system. The Council must adopt adaptive and innovative strategies to enhance the transparency and inclusiveness of its decision-making process and ensure its authority and efficiency in global governance. At the same time, the innovation of the global governance system requires the participation and contribution of wisdom from all countries to realize the democratization of global affairs and the rule of law through the principle of common cause and common sharing and to jointly build a community of shared destiny for humankind. This requires the international community to strengthen solidarity and cooperation, oppose confrontation and pressure, promote equality and mutual trust, oppose the hegemony of the powerful and work together to maintain an international order based on international law.